Identifying the Success Factors of the Brand Extension Case of Airbnb Experiences in Indonesia - Aurellia Widjaja; Mochammad Riyadh Rizky Adam (Institute of Computer Science (IOCS), 2021)
Airbnb launched an extension of its Stay product called Trip, which is rebranded and currently known as Experiences. Airbnb Experiences is aimed to complete Airbnb’s “belong anywhere” mission and promotes sustainable travel, which is believed able to solve problems like over-tourism. However, it hasn’t found any study on Airbnb Experiences in Indonesia; it could be subjectively assumed that the company may not have done any research as there was unconfirmed understanding about the current circumstances. There are also limited studies that have been done on brand extension in tourism marketplaces. This study aimed therefore to analyze the relationship between the parent brand, the perceived fit, and the consumer innovative approach to brand expansion and its impact on the purchase intention for Airbnb Experiences. This report was conducted on a wide range of issues. The study brought together 210 people through an online survey. There is a positive relationship between parent brand attitude and brand extension. The attitude of brand expansion is therefore most correlated to the perceived expansion value. The perceived value also influences the purchasing intentions positive and significant. On the other hand, this study shows that the attitude of the parent brand does not correspond to the perceived value directly or positively.